Il mito del paese di Cuccagna e la pubblicità televisiva italiana - Krnacka, Barbara (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
The article compares medieval and Renaissance literary descriptions of the mythic land of eternal bliss and prosperity Cuccagna with pictures and texts of Italian television advertisement of the nineties. The characteristic moments of these descriptions such as, for example, abundance, satisfying sensual needs, celebrating and feasting as well as the evaluation of the described phenomena, in these distant texts of culture, are very similar to each other. Italian television advertisement appears as another contemporary image of the land of bliss Cuccagna.
The myth of the land of Cuccagna and Italian television advertisement